THE INTELLIGIBILITY OF THAI ENGLISH PRONUNCIATION AMONG THAI ENGLISH TEACHERS - Siti Rahayu; Andi Syahputra; Sari Diana (FRASA: ENGLISH EDUCATION AND LITERATURE JOURNAL, 2026)
English has become a global language essential in education, diplomacy, and intercultural communication. Effective communication in English is increasingly dependent on intelligibility, the ease with which a listener can comprehend speech, rather than adhering to native-speaker norms. This study examines the intelligibility of Thai-accented English, focusing on four Thai English teachers at a kindergarten in Sadao, Thailand, as  perceived by four non-Thai listeners, specifically Indonesian student teachers participating in a teaching practicum (PPL). Data were collected from audio recordings of the teachers’ speech and semi-structured interviews with the listeners. Using a qualitative case study approach, the findings indicate that segmental features, such as the substitution of /r/ with /l/ (for example, rice pronounced as lice), and difficulties in reading passages were observed to lead to misunderstandings. Intelligibility was also influenced by both the speakers’ pronunciation and the listeners’ familiarity with Thai-accented English. This study contributes to the field of English as a Lingua Franca (ELF), highlighting that intelligibility rather than native-like pronunciation is key for effective intercultural communication.